If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+8+2x=2x+43
We move all terms to the left:
x+8+2x-(2x+43)=0
We add all the numbers together, and all the variables
3x-(2x+43)+8=0
We get rid of parentheses
3x-2x-43+8=0
We add all the numbers together, and all the variables
x-35=0
We move all terms containing x to the left, all other terms to the right
x=35
| 2(2x+6)=50 | | 0=x^2-10x-96 | | x/6-7=14 | | 7x-4=178 | | x+(3)=-14 | | x^2+13=14 | | 4m=-33/4 | | 4(2x-6)/32=(-3x-18)/24 | | -1.5=0.3x=-4.2 | | 2^x+7=32^x | | 3=1/8(-m-11) | | -14=-6=4v | | x+4=24-4 | | 2x^2-40x-150=0 | | 205=10-v | | 90=2x-18 | | 0=x^2+27x+72 | | 4x-2(-2x+8)=8 | | 1/6K=5/6k+13 | | 189=103-y | | 3(f-9)=18 | | 6+p=–6(–2p+10) | | m/6=(m+3)/10 | | 1-100x2=0 | | -12.8=y-16.4 | | 4.2-2=0.5(8.4x+6) | | −6=2(w+5) | | 5(2c+1)-(c+2)=-43 | | 3x+2(-x+3)=9 | | 1.5x+4=2x+24 | | -3y^2+18y-27=0 | | 144x-60=12(12x-5) |